Quality of care in frail older people: the fragile balance between receiving and giving. (25th March 2011) - Vernooij-Dassen, Myrra; Leatherman, Sheila; Olde Rikkert, Marcel
Abstract : The focus on providing essential medical and social care for frail older people often leaves them feeling unable to contribute. But building in reciprocation could help preserve social inclusion and foster autonomy, dignity, and quality of life, say Myrra Vernooij-Dassen, Sheila Leatherman, and Marcel Olde Rikkert